Zagregowane modele dyskryminacyjne i regresyjne w prognozowaniu czasu pobytu na OIOM pacjentów z chorobą wieńcową - Misztal, Małgorzata (Aggregation of Discriminant and Regression Models for Prediction of ICU Length of Stay Among Patients with Cad, 2008)
In the work [Misztal 2007] the classification and regression trees were applied to indicate preoperative risk factors associated with prolonged ICU stay among patients with coronary artery disease treated surgically. The results were not satisfying. The reason could be that single tree was not a stable classifier. The aggregation of classification or regression trees into the ensembles of classifiers can lead to a more accurate prediction. In the paper aggregated tree-based models (bagging, boosting, random forest, BART) are applied to improve the accuracy of the prediction of lCU length of stay among patients with CAD.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 316-322